Changes in the global P cycle in the Neoproterozoic recorded by the compositions of arc lavas - Sotiriou, Paul; Regelous, Marcel; Haase, Karsten (Chemical Geology, 2025)
The mafic lavas erupted at active subduction zones have higher P/Nd ratios than the bulk continental crust. This difference has been explained by the delamination of apatite-rich lower crust, transferring P from the crust to the mantle at subduction zones. Here we compile geochemical data from arc basalts (5.5–6.5 wt% MgO) that have formed in the last 2 Ga and show that Proterozoic arcs erupted basalts with lower average P6/Nd6 ratios than those of Phanerozoic fossil and active arcs. The P6/Nd6 ratios of active arc basalts are negatively correlated with Th6/La6 and positively correlated with Sr6/Th6, Ba6/Th6 and 143Nd/144Nd, indicating that high P6/Nd6 ratios in arc lavas are not inherited from subducted sediments, which generally have low P/Nd ratios. Phosphatised basaltic oceanic crust has high P contents and P/Nd ratios due to interaction with seawater, and metalliferous sediments deposited at active spreading ridges have very high P contents (2000–16,000 ppm) and P/Nd ratios (100–1456) due to coprecipitation of P with Fe-oxyhydroxides formed when reducing hydrothermal vent fluids mix with oxygenated deep ocean water. We propose that the lower P/Nd ratios of Proterozoic mafic arc lavas are the result of lower concentrations of P in seawater at that time. An increase in the P content of seawater at the end of the Proterozoic, coincident with the Neoproterozoic Oxygenation Event, is reflected in lower concentrations of P in marine sediments before 800 Ma, and in 1.3 Ga metalliferous sediments. The high P/Nd ratios of many young arc lavas are therefore not representative of those formed during most of Earth's history. Since most of the continental crust was formed before the end of the Proterozoic, less delamination of apatite-bearing lower crust may be needed to the explain the low P/Nd ratio of the bulk continental crust.
CRIS-Team Scopus Importer:2025-07-04
Keywords: Altered oceanic crust; Basaltic arc lavas; Global phosphorus cycle; Metalliferous sediments; Neoproterozoic; Siliciclastic marine sediments